TOD’S Station Area as catalyst of human movement and medium of preservation of urban heritage district at Old Town Butterworth - Mohamad Azlan, Zulhazriq Haniz (2018)
The paper reviews the uprising issues of lack of heritage preservation awareness in Old Town of Butterworth, Penang with an aim of to establish a Transit Oriented Development as the effort in promoting walkable environment for pedestrians thus, highlighting the heritage values located within the study area. This issue has been caused by a few other minor issues related to the morphological evolution of the town itself which are vehicular domination and site segregation which restricts human movement to the urban heritage area. The study involves a carefully conducted research on TOD’s principle and its suitability and the analysis on heritage building, space typology and preservation techniques. As a result, it is proven that the Old Town of Butterworth is highly suitable and capable in catering a new Transit Oriented environment as its new foundation which will encourage human movement within the study area and this redesign effort will eventually highlight all of the heritage values in the design.